Expression Pattern of Myelin-Related Apolipoprotein D in Human Multiple Sclerosis Lesions - Navarro, Ana; Rioseras, Beatriz; del Valle, Eva; Martínez-Pinilla, Eva; Astudillo, Aurora; Tolivia, Jorge (Frontiers in Aging Neuroscience, 2018)
Apolipoprotein D (Apo D) is a key molecule in the lipid transport during homeostasis and repair processes in normal and pathological conditions of the nervous system with a putative neuroprotective effect. In the last decades, huge experimental efforts have been made to know the exact mechanism of action of Apo D, even though, it remains an open question. In this regard, studies in mammals and flies have suggested that Apo D seems to act through a variety of cellular mechanisms related with its ability to selectively bind different lipid ligands. For instance, this apolipoprotein is required to myelin compaction, it participates in axon regeneration/remyelination, and it can control the magnitude and timing of the inflammatory response after injury, promoting myelin clearance and regulating the number of immune cells recruited to the damaged area. These, among others, are some of the reasons to study Apo D in multiple sclerosis (MS) pathology, where it could be of particularly important since the autoimmune reaction against oligodendrocytes and myelin is generally assumed as the most plausible cause of this pathology. The aim of this work was to investigate the Apo D expression pattern in MS lesions, including active and inactive demyelinating plaques, and also remyelinating ones. Human brain tissues with inflammatory demyelination consistent with MS were used to quantifying Apo D immunosignal in different lesions. Our results show a clear decrease of Apo D expression in all sclerosis plaques, being lower in the inactive than in active areas but recovers in the remyelination ones. Apo D is mainly produced by the matured oligodendrocytes of white matter and is located in cell processes surrounding the myelin sheath. All these data seem to indicate an important role of Apo D in myelination/remyelination processes as a molecule with a neuroprotective potential, and may serve as a good starting point for its study in MS.